An Adjustable‐Porosity Plastic Crystal Electrolyte Enables High‐Performance All‐Solid‐State Lithium‐Oxygen Batteries. (14th April 2020) - Wang, Jin; Huang, Gang; Chen, Kai; Zhang, Xin‐Bo
Abstract: The limited triple‐phase boundaries (TPBs) in solid‐state cathodes (SSCs) and high resistance imposed by solid electrolytes (SEs) make the achievement of high‐performance all‐solid‐state lithium‐oxygen (ASS Li‐O2 ) batteries a challenge. Herein, an adjustable‐porosity plastic crystal electrolyte (PCE) has been fabricated by employing a thermally induced phase separation (TIPS) technique to overcome the above tricky issues. The SSC produced through the in‐situ introduction of the porous PCE on the surface of the active material, facilitates the simultaneous transfer of Li + /e −, as well as ensures fast flow of O2, forming continuous and abundant TPBs. The high Li + conductivity, softness, and adhesion of the dense PCE significantly reduce the battery resistance to 115 Ω. As a result, the ASS Li‐O2 battery based on this adjustable‐porosity PCE exhibits superior performances with high specific capacity (5963 mAh g −1 ), good rate capability, and stable cycling life up to 130 cycles at 32 °C. This novel design and exciting results could open a new avenue for ASS Li‐O2 batteries. Abstract : Holey cathodes, Battman ! An adjustable‐porosity plastic crystal electrolyte (PCE) has been fabricated to solve the problems of high resistance and limited triple‐phase boundaries in all‐solid‐state lithium‐oxygen (ASS Li‐O2 ) batteries. The ASS Li‐O2 battery with dense PCE and porous PCE‐based solid‐state cathode shows ultra‐low resistance (115 Ω), large capacity (5963 mAh g −1 ), good rate capability, and long cycle life (130 cycles) at 32 °C.